Evaluation of Speaking Curriculums at the Erbil Private Universities using Context, Input, Process and Product model - Lava Noori Ali; Suleyman Celik (QALAAI ZANIST SCIENTIFIC JOURNAL, 2020)
The purpose of this study is to explain the effectiveness of the Speaking curriculum in English Language Teaching (ELT) Department in Private Universities in Erbil, Iraq. The theoretical background behind this evaluation study is Stufflebeam’s evaluation model (1983), CIPP, Context, Input, Process and Product. Students’ and instructors’ perspectives are taken regarding the studying goals and objectives, used teaching methodologies, studying environment, materials and assessments of the courses. This study will help teachers to find out more engaging ways of teaching that focus on using the language more fluently and accurately rather than memorization. The objective of this study is to recommend necessary changes, adaptions, or improvements required for the university curriculums. Participants were English department 169 students and 11 teachers in three private universities of Erbil-Iraq. The results showed that the speaking courses are satisfactory but they need some minor changes and improvements regarding course goals and objectives, course materials and instrumentation in order to obtain a better curriculum to fulfill the students’ and teachers’ expectations of the course.